STUDI KOMUNITAS NYAMUK PENYEBAB FILARIASIS DI DESA BOJONG KABUPATEN LAMPUNG TIMUR - Zen, Suharno (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
Filariasis is a disease caused by species of filarial worms Wuchereria bancrofti, Brugia malayi and Brugia timori and spread by the Anopheles mosquito, and Culex sp Mansonia sp. It is known that nematodes cause filariasis in District Sekampung Udik East Lampung district are a species Brugia sp. This study was conducted in one of the houses in the village of Bojong filariasis patients in March-May 2013. The arrest of mosquitoes made 1 times a week for 1 month from the hours 18: 00-06: 00. The method used for catching mosquitoes is to use bait human foot (human landing) for 20 minutes, and break every 5 minutes. The arrest was made by investigators assisted by two local residents by using the tool aspirometer. Mosquitoes were then taken to the Laboratory of Parasitology Entomology section of the Faculty of Medicine, the University of Gadjah Mada in Yogyakarta for mosquitoes identified using identification keys. Besides observations to the environmental conditions around the homes of people. From the results obtained in 1020 catching mosquitoes which consists of seven species of mosquito that is; Culex tritaeniorhynchus (420), Cx. fasciatus (48), Mansonia uniformis (152), Ma. dives (56), Ma. annulifera (4), Ma. annulata (4) and mosquito Anopheles (336). State of the environment in the village of Bojong subdistrict Sekampung Udik the form fields as rubber, cocoa, swamps, paddy fields potentially provide breeding grounds for mosquitoes filariasis. Further research is needed to determine the value of microfilaria rate and mosquito vector bionomics of filariasis.Kata kunci : filariasis, identifikasi, Â human landing, mikrofilaria rateÂ